Bahasa Sebagai Cermin Identitas Analisis Perspektif Martin Heidegger - Reiginayossi, Midori; Sitorus , Fitzerald Kennedy (CV. ITTC INDONESIA, 2023)
This study delves into Martin Heidegger's perspective on language as an embodiment of identity that surpasses mere communication tools. From Heidegger's standpoint, language not only conveys objective meaning but also shapes one's worldview and self-identity. This analysis explores how language, within Heidegger's perspective, forms the interpretative foundation for individuals, influencing perceptions of truth and playing a central role in shaping cultural and social self-identities. This inquiry views language as a mirror reflecting the profound aspects of human identity and offers insights into how Heidegger's conception can guide a richer interpretation of the relationship between language and identity.